2009
DOI: 10.1603/029.102.0346
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide Susceptibility of <I>Euschistus heros</I> (Heteroptera: Pentatomidae) in Brazil

Abstract: Euschistus heros (F.) (Heteroptera: Pentatomidae) is the most prevalent stink bug pest in Brazil, and populations can be difficult to manage using organophosphates or endosulfan. Because E. heros is difficult to rear in the laboratory, no baseline insecticide susceptibility data have been published. Therefore, we conducted dose-mortality studies using field-collected insects, and, using the results from the dose-mortality studies, we surveyed susceptibility to acephate, methamidophos, and endosulfan in populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 6 publications
4
34
0
8
Order By: Relevance
“…However, populations of this pentatomid are difficult to manage using organophosphates (methamidophos, acephate, chlorpyrifos, and monocrotophos) or cyclodiene endosulfan (Sosa-Gómez et al, 2009). Consequently, control strategies are based on spraying using a limited group of insecticides (Sosa-Gómez et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, populations of this pentatomid are difficult to manage using organophosphates (methamidophos, acephate, chlorpyrifos, and monocrotophos) or cyclodiene endosulfan (Sosa-Gómez et al, 2009). Consequently, control strategies are based on spraying using a limited group of insecticides (Sosa-Gómez et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Sosa-Gómez et al (2009) evaluated the activity of esterases in populations of E. heros in the Brazilian states of Paraná and São Paulo using α-naphthyl acetate as a substrate, and found significant variation in esterase activity in these populations. The present study also found six different types of esterase in these insects that are capable of hydrolyzing α-naphthyl acetate.…”
Section: Discussionmentioning
confidence: 99%
“…Among the species most frequently found on soybeans, Euschistus heros (F.) (Heteroptera: Pentatomidae) are considered the most relevant pests in the main productive regions of Brazil (Sosa-Gómez et al 2009). The large populations of these insects and the lack of action-level usage of insecticides frequently leads to the indiscriminate use of chemical products to control of these insects (Corrêa-Ferreira 2005).…”
Section: Introductionmentioning
confidence: 99%